2019
DOI: 10.1037/prj0000321
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of perceived social effectiveness of individuals with serious mental illness.

Abstract: Objective: Social effectiveness continues to play a critical role in recovery of people with serious mental illness (SMI), with greater social effectiveness predicting many positive life outcomes. Despite the abundance of literature supporting the relationship between perceptions and behavior, little is known about predictors of perceived social effectiveness of individuals with SMI. Methods: The purpose of this study is to examine the predictors of perceived social effectiveness of individuals with SMI. Cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 103 publications
(143 reference statements)
0
3
0
Order By: Relevance
“…35 Sánchez and colleagues declared that the inability to accept disability was a significant barrier to individual productivity and social functioning. 36 Additionally, this study revealed that individuals with schizophrenia have their own vision and expectations of life as well as the potential to live a meaningful life. Some of the participants dreamt of achieving their academic and career goals and even starting their own businesses; however, receiving suggestions for how their rehabilitation should proceed adversely affected their interests.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…35 Sánchez and colleagues declared that the inability to accept disability was a significant barrier to individual productivity and social functioning. 36 Additionally, this study revealed that individuals with schizophrenia have their own vision and expectations of life as well as the potential to live a meaningful life. Some of the participants dreamt of achieving their academic and career goals and even starting their own businesses; however, receiving suggestions for how their rehabilitation should proceed adversely affected their interests.…”
Section: Discussionmentioning
confidence: 80%
“…Literature indicates that a lack of insight can impede productivity, and the achievement of insight should be the first step towards rehabilitation 35 . Sánchez and colleagues declared that the inability to accept disability was a significant barrier to individual productivity and social functioning 36 …”
Section: Discussionmentioning
confidence: 99%
“…Literature also indicates that lack of insight can impede productivity, and achievement of insight should be the first step towards rehabilitation (Jong et al, 2019). Sánchez et al (2019) also declared that the inability to accept disability was a significant barrier to individual productivity and social functioning. C1Av was asked to sing, and he sang one of his tracks titled 'There are many people in bondage.…”
Section: Discussionmentioning
confidence: 99%